WATER FILTERATION USING THE COCONUT SHELL AND NEEM LEAF - P. S. Shinde,; Prof. A. B. Landage, (International Journal of Innovations in Engineering Research and Technology, 2024)
Due to the demand for high-quality water in people's daily lives, water quality has currently become a serious issue. There are numerous ways to enhance water. As more than a billion people on earth, in rural area water purification technologies have developed over the past few centuries to preserve public health. No one on this planet has access to pathogen-free, safe drinking water. India is among inhabited nations in the world where the poor cannot afford a portable, clean water source quality. Surface water is treated using a set of filters made of local materials. The effectiveness of single media and dual media was examined in the study of media to eliminate turbidity, color, and germs.Along to minimize this problem there are permanent solution needed. But now days in rural areas its big issue to purifying drinking water with simple technics. Also, government have an over burden of this issue. The government gives efforts for water purification scheme in rural areas. But such scheme includes the modern technics of water purification like a water treatment plant [WTP], or online pressure filter. Such modern technics government gives initial funds but after implementation of such technics there have a some frequently maintenance required. For this maintenance government cannot having suitable funds. That’s reason this all maintenance cost bear by the local government bodies like gram panchayat. But those bodies cannot have suitable income for implement of scheme in future, so such schemes are discontinued and a person drinks the contaminated water. Its big issue for their health so now days it’s important to develop the convenient and budget friendly technic for purification of drinking water.Due to this reason we are develop the water purification filter with the help of coconut shell and neem, in very pocket friendly budget